Gastro Scholar & Ventures / Muhammad Anuar Salleh - Salleh, Muhammad Anuar (Faculty of Business and Management, 2023)
My memorable and enlightening 6-month industrial training began here at Gastro Scholar & Ventures. This internship report details my internship period that I have finished in Gastro Scholar & Ventures, which started on March 1st, 2023, and ends August 15th, 2023. The main service that Gastro Scholar & Ventures offer is providing a LEGAL platform for students to carry out consultancy work, supply and provision of food and beverage services. The other service is F&B services which this company will be involved in offering services related to the supply and preparation of food and beverages. Gastro Scholar & Ventures also offer training services related to food and beverage services for the development of competence of staff, students and interested external parties. During the 6 months of industrial training, I had the opportunity to perform tasks and work well guided by my supervisor. I am able to apply some of the knowledge I learned at university and put it into practice at work. I was also placed at Caffeine & Calories (C&C), a brand under Gastro Scholar to do work such as opening the kiosk as early as 8 a.m. and supervising and monitoring sales every day. I also got guidance from 3 UTHM students who are baristas for C&C kiosks on how to operate a business, deal with stock-related sellers and how to promote products to UTHM staff and students. As you will see, the strength of Gastro Scholar & Ventures is their SWOT analysis. In addition, we have business networking with industry players and our company obtains university assistance in terms of knowledge, expertise and facility. The latter are weaknesses, which are insufficient financial resources and unsatisfactory social media initiative which needs to be overcome by Gastro in order to survive in business. Gastro also has several opportunities including business collaboration opportunities with potential strategic partners and franchise potential outside the university area. Not only opportunities, threats which are external factors are also likely to be faced by Gastro. The threats are such as stiff competitions from other businesses and the operational cease.